2005
DOI: 10.1073/pnas.0503069102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac implications of increased arterial entry and reversible 24-h central and peripheral norepinephrine levels in melancholia

Abstract: The mortality of chronic heart failure (CHF) doubles either when CHF patients are depressed or when their plasma norepinephrine (NE) level exceeds those of controls by Ϸ40%. We hypothesized that patients with major depression had centrally driven, sustained, stress-related, and treatment-reversible increases in plasma NE capable of increasing mortality in CHF patients with depression. We studied 23 controls and 22 medication-free patients with melancholic depression. In severely depressed patients before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 25 publications
2
68
0
6
Order By: Relevance
“…mental health-care practice, reflects the general population of depressed and anxiety patients. Several reports using different SNS indices also found increased sympathetic activity in depressed or anxious subjects (Esler et al, 1982;Gold et al, 2005;Guinjoan et al, 1995;Light et al, 1998;Koschke et al, 2009). These previous reports focused on general sympathetic activity, whereas we measured sympathetic control more narrowly by its effects on cardiac contractility.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…mental health-care practice, reflects the general population of depressed and anxiety patients. Several reports using different SNS indices also found increased sympathetic activity in depressed or anxious subjects (Esler et al, 1982;Gold et al, 2005;Guinjoan et al, 1995;Light et al, 1998;Koschke et al, 2009). These previous reports focused on general sympathetic activity, whereas we measured sympathetic control more narrowly by its effects on cardiac contractility.…”
Section: Discussionmentioning
confidence: 81%
“…Various studies reported increased sympathetic activity in depressed and anxious subjects compared with healthy controls, measured by different indices like spillover of norepinephrine (NE) and epinephrine (EPI), skin conductance responses, QT interval variability (QTvi), or the pre-ejection period (PEP) (Light et al, 1998;Esler et al, 1982;Guinjoan et al, 1995;Gold et al, 2005;Koschke et al, 2009;Barton et al, 2007). However, other studies reported no association between psychopathology and SNS activity or reported decreased SNS activity in subjects with depressive or anxiety disorders (Wilkinson et al, 1998;Esler et al, 2004;Roth et al, 2008;Ahrens et al, 2008), so findings remain inconclusive.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…36 Sympatho-adrenal dysregulation is another common finding in depressed subjects, as evidenced by increased catecholamine turnover and increased catecholamine urinary excretion in severe depression. 37,38 The coexisting dysregulation of HPA and sympatho-adrenal axes in depression may result from a defect at or above the level of the hypothalamus, leading to hypersecretion of corticotropin-releasing hormone (CRH). Interestingly enough, ACTH response to exogenous ovine CRH is attenuated in depression, suggesting that the pituitary corticotroph cell is restrained by the negative feedback of glucocorticoids.…”
Section: Depression and Osteoporosis In Men: Association Or Casual Link?mentioning
confidence: 99%
“…It has been proposed that enhanced cortisol agonistic effects during depressive episodes may contribute to an elevation in MAO-A levels (53). Severely depressed patients had significant increases in blood pressure, CSF and plasma NE, as well as elevated plasma cortisol (115). Notably, elevated platelet MAO activity associated with increased cortisol levels has been described in depression; platelet MAO activity has also been associated with severity of depressive symptoms (116).…”
Section: Increased Mao-a Activity As a Factor Linking Depression Withmentioning
confidence: 99%